2014
DOI: 10.1074/jbc.m114.564021
|View full text |Cite
|
Sign up to set email alerts
|

The Solution Structure, Binding Properties, and Dynamics of the Bacterial Siderophore-binding Protein FepB

Abstract: Background: FepB is a periplasmic binding protein that transports the catecholate siderophore enterobactin. Results: The solution NMR structures of apo-and holo-FepB were solved revealing a unique siderophore binding mechanism. Conclusion: Enterobactin binding involves the ordering of dynamic loop residues. Significance: The binding of enterobactin by FepB does not proceed by the typical Venus flytrap scheme.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(31 citation statements)
references
References 91 publications
1
30
0
Order By: Relevance
“…For instance, in bacterial importer MalFGK2, the transporter rests in an inward-open conformation and switches to outward-open upon MBP and ATP binding (27). For YbtPQ, although no specific SBP has been identified, one possibility is that SBPs from other siderophore uptake systems may be used here, for example, FepB of the enterobactin uptake system (36) and FhuD of the hydroxamate siderophore uptake system (37). Once SBP delivers the substrate to the transporter, YbtPQ's conformational transition happens, which will effectively stimulate ATP binding and hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, in bacterial importer MalFGK2, the transporter rests in an inward-open conformation and switches to outward-open upon MBP and ATP binding (27). For YbtPQ, although no specific SBP has been identified, one possibility is that SBPs from other siderophore uptake systems may be used here, for example, FepB of the enterobactin uptake system (36) and FhuD of the hydroxamate siderophore uptake system (37). Once SBP delivers the substrate to the transporter, YbtPQ's conformational transition happens, which will effectively stimulate ATP binding and hydrolysis.…”
Section: Discussionmentioning
confidence: 99%
“…For Gram-positive bacteria, these include EntS-type major facilitator superfamily (MFS) exporter and import through a FepCDG-like multifunctional ABC transporter system associated with a FepB-like transporter through the ligand exchange mechanism. 33,34,35 Imported ferric iron bound to siderophore must be released to be made available to cellular machinery. One strategy for iron release is through hydrolytic destruction of the siderophore by esterases of the α,β-hydrolase family of enzymes, represented by the E. coli fes, iroD and iroE gene products and is a common strategy for macrolactone-based siderophores.…”
Section: Introductionmentioning
confidence: 99%
“…The equilibrium between open and closed conformations of E. coli periplasmic ligand binding proteins has previously been investigated by solution NMR spectroscopy for the maltose binding protein (Tang et al 2007), the glutamine binding protein (Bermejo et al 2010), the histidine binding protein (Chu et al 2013), the siderophore binding protein (Chu et al 2014), and the ribose and glucose/galactose binding proteins (Ortega et al 2012 In the case of DEBP, the PCSs confirm that the glutamate-bound protein assumes the closed structure observed in the crystal structure of the S. flexneri homologue. In contrast to the DEER data, which indicated that the closed conformation is predominantly populated even in the absence of glutamate (Abdelkader et al 2015), the changes in chemical shifts as well as PCSs indicate that the transition to the substrate-free protein involves a movement of the domains as rigid entities relative to each other.…”
mentioning
confidence: 82%